Evaluation of growth performance, feed efficiency and nutrient digestibility of red hybrid tilapia fed dietary inclusion of black soldier fly larvae (Hermetia illucens) - Hasniyati Muin; Norhidayah Mohd Taufek (Aquaculture and Fisheries, 2024)
Insects, particularly black soldier fly larvae (BSFM), Hermetia illucens, have been regarded as promising protein and lipid sources in animal feed, including fish. Digestibility is the key factor that affects nutrient utilization, feeding physiology and efficiency. In the present work, the effect of BSFM on the digestibility of red hybrid tilapia (RHT) compared to fish meal (FM) was ultimately unveiled. A 56-day growth trial was performed with 60 RHT (∼30 g) randomly distributed into six tanks and fed two experimental diets containing FM as a reference diet and BSFM as a test diet. In addition, faeces were collected to determine their chromium concentration and proximate composition. The apparent digestibility coefficient (ADC) of dry matter, crude protein and energy in the BSFM diet were observed to be significantly higher than those in the FM diet. Besides, the growth performance of fish fed with the BSFM diet exhibited significantly higher (P < 0.05) weight gain, specific growth rate, protein efficiency ratio and lower feed conversion ratio than those in the FM group. This study shows that the BSFM feed was well digested by tilapia and improved its growth performance.